Implementasi Nilai-Nilai Sibaliparri’ Di Masyarakat Pesisir Kabupaten Majene Sulawesi Barat (Tinjauan Living Qur’an dan Hadis) - Nasir, Muhammad; Marsyam, Abdul Waris; Nurianti HS (Al-Ulum, 2025)
This research examines the implementation of Sibaliparri values (a local mutual assistance ethic) in coastal communities in Majene Regency, West Sulawesi with a review of the Qur'an and Hadith analyzed using a phenomenological approach. Sibaliparri represents a mutual assistance ethic in all situations such as Palluluareang (brotherhood), Siasayangngi (compassion), Sianauang pa'mai (care) and Sukku' Mattulung, covering both material and spiritual aspects in Islamic values. Coastal communities primarily engaged in fishing must adopt adaptation strategies to address diverse life challenges, including by integrating Sibaliparri values into their social life. The research method used is a qualitative-descriptive to describe the meaning of lived experiences. The results showed that Sibaliparri is interpreted with various meanings, including; as an expression of gratitude, mutual cooperation and social solidarity, practicing Islamic teachings, economic activities, and manifestations of love and affection.